Rhinitis in Swimmers: A Clinical Issue at the Intersection of Sports Medicine and Otorhinolaryngology - Matyja, Mateusz; Kowalska, Marta; Mazur, Anna; Brodziak, Julia; Fojcik, Katarzyna; Ciszewska, Wiktoria; Kosztyła-Czech, Zofia; Wiśniewski, Tomasz; Dworak, Michał (Quality in Sport, 2025)
The development of rhinitis in swimmers is multifactorial. Contact with disinfection byproducts plays a role in the pathogenesis of swimmer’s rhinitis, leading to irritation, increased epithelial permeability, and the development of mucosal hyperreactivity, which promotes the dominance of the non-allergic irritant rhinitis phenotype in competitive swimmers. A significant deterioration in quality of life has been demonstrated in swimmers with rhinitis, as assessed using validated scales, in particular the miniRQLQ. The review emphasises the role of chronic exposure to the swimming pool environment as a modifiable risk factor and indicates that limiting contact with irritants – through the use of swimming clips, optimising ventilation, and improving water quality – can lead to reduced symptom severity and partial reversibility of changes in the nasal mucosa. Attention was drawn to the significant heterogeneity in definitions and diagnostic criteria in the literature, which makes it difficult to assess the disease’s prevalence and mechanisms clearly.